2020
DOI: 10.20944/preprints202006.0006.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Impact on Children's Mental Health of School Closures to Prevent the Spread of the Novel Coronavirus (COVID-19)

Abstract: In Japan, schools were suddenly closed all over the country with one month left at the end of the school year to prevent the spread of new coronavirus infections. Although previous studies have shown that quarantine and isolation have a negative impact on mental health, the impact of school closure on children's mental health is not clear. This study examined mental health indicators, such as emotional symptoms, in addition to behavior during school closure and anxiety after school resumes, among children in t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Furthermore, beyond typical findings on family processes, we found that the child distance learning workload (as perceived by the parents) significantly predict child behavioral difficulties, extending previous findings about the potential negative effects of homeschooling on children's experience (Ishimoto et al, 2020; Thorell et al, 2021). This could be related to the difficulty of learning from new digitally mediated practice, as well as to the decreased support received from the teachers and the schoolmates.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, beyond typical findings on family processes, we found that the child distance learning workload (as perceived by the parents) significantly predict child behavioral difficulties, extending previous findings about the potential negative effects of homeschooling on children's experience (Ishimoto et al, 2020; Thorell et al, 2021). This could be related to the difficulty of learning from new digitally mediated practice, as well as to the decreased support received from the teachers and the schoolmates.…”
Section: Discussionsupporting
confidence: 86%
“…The social and economic impact of pandemics on children and families has been explored by many studies (Chen et al, 2011;Esposito et al, 2011;Principi et al, 2003); however, the literature provides scant insight into the effects of pandemics on education and social problems of preschool children in particular, as well as parents' difficulties caring for children during such periods. Previous studies (Basurto-Dávila et al, 2013;Gift et al, 2010;Miller et al, 2010;Wong et al, 2014;Ishimoto et al,2020) in this area have generally focused on the experiences of primary and high school students. The COVID-19 pandemic has revealed the lack of research on preschool children's experiences during pandemics.…”
mentioning
confidence: 99%